2003
DOI: 10.1103/physrevb.68.153202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetophotoluminescence of quantum confined states in orderedGaxIn1xPwith

Abstract: We observe the diamagnetic shift and Zeeman splitting of ultra-sharp photoluminescence lines which appear in an ordered-GaInP epilayer using a micro-photoluminescence technique in fields up to 5 T. These transitions show many signatures of a fully quantum-confined state, however, a detailed description of the origin of these states is not known. Under a magnetic field, these states show behavior similar to other III-V quantum dot systems, with large variations in diamagnetic shift and exciton g factor. By noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…5͒. The experiments were carried out in a He 4 -bath cryostat at 4.2 K, using an argon-ion laser at a wavelength of 514 nm to excite the electrons. The photoluminescence ͑PL͒ was analyzed by a spectrometer and an intensified chargedcoupled-device detector, using an integration time of 0.5 ms.…”
Section: Magnetoexciton Transitions and Comparison Between Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…5͒. The experiments were carried out in a He 4 -bath cryostat at 4.2 K, using an argon-ion laser at a wavelength of 514 nm to excite the electrons. The photoluminescence ͑PL͒ was analyzed by a spectrometer and an intensified chargedcoupled-device detector, using an integration time of 0.5 ms.…”
Section: Magnetoexciton Transitions and Comparison Between Theorymentioning
confidence: 99%
“…To explore these QD properties, optical spectroscopy experiments in the presence of an external magnetic field is a good probing tool. 4,5 Semiconductor QDs can be grown by many methods, but in most cases are based on lithography and self-organization techniques. Self-assembled QDs formed through the Stranski-Krastanow growth mode, among the various 0D systems investigated so far, are the most well studied QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning near field spectroscopy combined with TEM has suggested that the low-energy emission does not correlate with APBs, since a number of low-energy lines with different energies were emitted from small areas both on and off long-extended APBs. 9,10 This paper showed that small domains of SLs bounded by APBs, that are observable by XSTM but not observed clearly by TEM, exist in the "large domains" bounded by long-extended APBs that are distinctly observable by TEM, and no defect except APBs was observed. It is theoretically expected that the photon energy of the low-energy light emitted from a disk-like InP layer depends on the size of the disk.…”
mentioning
confidence: 90%
“…9 Measurements showed that the very long lifetimes of the LEB PL did not extend also to the LEL, 8,10 and thus, a model of a type-II quantum disk was not supported. Furthermore, it was argued 8 that the APBs, which are spatially quite dilute in large-domain samples, could not be the source of spectral components that exist throughout the entire sample.…”
Section: Introductionmentioning
confidence: 96%